Diesel exhaust particle role on gut microbiome and onset of Alzheimer disease neuroinflammation: Health services research / Policy and plans. (7th December 2020) - Naughton, Sean X; Westfall, Susan; Pasinetti, Giulio Maria
Abstract: Background: Recent evidence has emerged to show that diesel exhaust particulate (DEP) pollution can double the risk of getting dementia. Evidence suggest that exposure to high levels of air pollution are significantly more likely to develop dementia‐related diseases including Alzheimer's disease. DEP is primarily composed of polycyclic aromatic hydrocarbons (PAHs) and nitro‐substituted polycyclic aromatic hydrocarbons (n‐PAHs). PAHs have previously been shown to undergo biotransformation through interactions with human colonic microbiota. The goal of the present study is to determine if DEP may influence selective gut microbiota. We will eventually identify gut‐brain‐axis mechanisms associated with DEP mediated neuroinflammatory mechanisms through microbiota dysbiosis. Method: Using an in vitro model of the human gastrointestinal tract, EBIOME, we are exploring the human gut bacteria exposed to various concentrations of diesel exhaust particulate matter. Bacterial species were quantified over an extended time‐course to monitor log‐scale changes in colony survival and growth. In order to obtain higher resolution of gut microbiome species meta‐genomic analysis will be also conducted. Result: The current studies have identified concentration dependent changes in microbiome biodiversity. Through ongoing analysis, it is anticipated that altered biodiversity will lead to decreases in the production of brain penetrant metabolites, such as short‐chain fatty acids including butyrate, acetate, and propionate. Conclusion: Our studies provide novel information regarding the role of the gut‐brain‐axis in neuroinflammation in Alzheimer's disease and other forms of dementia.